The mediating/moderating role of cultural context factors on self-care practices among those living with diabetes in rural Appalachia - Brittany L. Smalls; Adebola Adegboyega; Ellen Combs; Matthew Rutledge; Philip M. Westgate; Md. Tofial Azam; Felipe De La Barra; Lovoria B. Williams; Nancy E. Schoenberg (BMC, 2021)
Abstract Background The aim of this study was to examine whether cultural factors, such as religiosity and social support, mediate/moderate the relationship between personal/psychosocial factors and T2DM self-care in a rural Appalachian community. Methods Regression models were utilized to assess for mediation and moderation. Multilevel linear mixed effects models and GEE-type logistic regression models were fit for continuous (social support, self-care) and binary (religiosity) outcomes, respectively. Results The results indicated that cultural context factors (religiosity and social support) can mediate/moderate the relationship between psychosocial factors and T2DM self-care. Specifically, after adjusting for demographic variables, the findings suggested that social support may moderate the effect of depressive symptoms and stress on self-care. Religiosity may moderate the effect of distress on self-care, and empowerment was a predictor of self-care but was not mediated/moderated by the assessed cultural context factors. When considering health status, religiosity was a moderately significant predictor of self-care and may mediate the relationship between perceived health status and T2DM self-care. Conclusions This study represents the first known research to examine cultural assets and diabetes self-care practices among a community-based sample of Appalachian adults. We echo calls to increase the evidence on social support and religiosity and other contextual factors among this highly affected population. Trial registration US National Library of Science identifier NCT03474731. Registered March 23, 2018, www.clinicaltrials.gov .